Prolonged theoretical classes impact students’ perceptions: an observational study - Kotnik, Petra; Roelands, Bart; Bogataj, Špela (Frontiers in Psychology, 2024)
Mental fatigue (MF) arises during prolonged demanding cognitive activity and results in acute feelings of tiredness and a decreased physical and/or cognitive performance capacity. An often-overlooked population that is significantly at risk for the development of MF are university students. The current study investigated the impact of prolonged in-person theoretical classes on the perceptions of MF, boredom, and sleepiness among 27 Slovenian university students (first-year physiotherapy). Their subjective experiences at various time points during a 4-hour class interspersed with a 20min break were assessed with a repeated measures ANOVA and consequent Bonferroni post-hoc tests (significance set at <0.05). Subjective MF and sleepiness significantly increased during the first and the second part of the class (p<0.05), while they significantly decreased during the break (p<0.05). Boredom levels only increased significantly during the second part of the class (p<0.05). Additionally, students who had inadequate sleep the night before the class reported higher levels of MF at the beginning of the class. This study highlighted a significant impact of a theoretical class on subjective feelings of mental fatigue and showed that a break in the middle of the class temporarily alleviated this negative impact. These results emphasize the importance of adequate sleep, effective breaks, and strategies to manage cognitive workload in optimizing students' cognitive well-being and academic performance. Further research is needed to better understand the underlying factors and develop targeted interventions to support students' cognitive functioning and well-being during prolonged academic sessions.